The Influence of Workload and Work Environment: How Employees Achieve Optimal Performance - Pitrianti, Pipit; Ananta Vidada, Irwin (SAN Scientific, 2025)
The work environment at PT Palapa Property Indonesia is not too spacious, with a slightly excessive employee population. This condition certainly impacts the less stable performance of employees in property sales in the last three years. The company always wants to improve employee performance every year, but the results obtained are a decrease in employee sales, which can be seen from 2021 to 2023. This study aims to explain the partial and simultaneous influence of workload and work environment variables on employee performance at PT Palapa Property Indonesia. This type of research is quantitative because it relates to numbers and statistics to test variables and hypotheses. This study showed that workload has a partial and significant adverse effect on employee performance. The work environment has a partial and significant effect on employee performance. Workload and work environment have a simultaneous effect on employee performance. Managerial implications that organizations need to ensure that the workload given is balanced and supported by a work environment that supports productivity, such as adequate work facilities, good interpersonal relationships, and policies that pay attention to employee welfare.